ARDS onset time and prognosis: is it a turtle and rabbit race? - Chiumello, Davide; Marino, Antonella (Journal of Thoracic Disease, 2017)
According to the last Berlin definition, ARDS is a form of acute diffuse lung injury occurring in patients with predisposing risk factors, onset within one week of a known clinical insult or new/worsening respiratory symptoms, presence of bilateral opacities on the chest radiographs not fully explained by effusions, lobar/lung collapse, or nodules, respiratory failure not fully explained by cardiac failure or fluid overload, and hypoxemia. It can be classified as mild (200 mmHg < PaO2/FiO2 ≤300 mmHg or 27 kPa < PaO2/FiO2 ≤40 kPa), moderate (100 mmHg < PaO2/FiO2 ≤200 mmHg or 13 kPa < PaO2/FiO2 ≤27 kPa) or severe (PaO2/FiO2 ≤100 mmHg or PaO2/FiO2 ≤13 kPa) (1).